2014
DOI: 10.1037/spq0000044
|View full text |Cite
|
Sign up to set email alerts
|

Predictive relations between peer victimization and academic achievement in Chinese children.

Abstract: The goal of this study was to explore longitudinal associations between peer victimization and academic achievement in Chinese children. Participants were N = 805 3rd-grade students (486 boys, 319 girls; M(age) = 9.5 years, SD = 3 months) attending primary schools in Shanghai, People's Republic of China. At Time 1 and Time 2 (2 years later), peers nominated classmates who were victims of peer maltreatment using the Chinese version of the Revised Class Play (Chen, Rubin, & Sun, 1992), and teachers rated student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 50 publications
2
33
0
2
Order By: Relevance
“…An index of peer preference was then formed by subtracting negative nomination scores from the positive nomination scores (Coie, Dodge, & Coppotelli, 1982). These peer nomination procedures have been used and proved valid with Chinese children (Chen et al, 1995;Liu, Bullock, & Coplan, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An index of peer preference was then formed by subtracting negative nomination scores from the positive nomination scores (Coie, Dodge, & Coppotelli, 1982). These peer nomination procedures have been used and proved valid with Chinese children (Chen et al, 1995;Liu, Bullock, & Coplan, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…To begin with, as in Western cultures, elevated but sub-clinical symptoms of internalizing problems are (in and of themselves) associated with concurrent and subsequent adjustment difficulties among Chinese children (e.g., Chen, Wang, Li, & Liu, 2014;Liu et al, 2015). Similarly, victimization and peer dislike are also substantive predictors of negative well-being in Chinese children (e.g., Chan, 2013;Liu, Bullock, et al, 2014). Moreover, academic and school difficulties are particularly problematic for Chinese children, given the extremely high value placed on academic achievement in this culture (Yang, Chen, & Wang, 2014).…”
Section: Implications Of Social Withdrawal In Chinamentioning
confidence: 97%
“…For example, the experience of negative peer relationships appears to increase children's vulnerability for depression (Schwartz et al ., , ). However, depression may also affect children's abilities to positively interact with their peers, thereby increasing risk for victimization (e.g., Kochel et al ., ; Vaillancourt et al ., ), which in turn may promote academic difficulties (e.g., Liu et al ., ; Schwartz et al ., ). Depression may also directly predict lower achievement (Chen et al ., ; Riglin et al ., ), although there is also evidence to suggest that lower achievement also directly predicts future depression (e.g., Vaillancourt et al ., ; Yong et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…Results from several studies have indicated that peer victimization also predicts later academic difficulties among Western children (Iyer, Kochenderfer‐Ladd, Eisenberg, & Thompson, ; Juvonen, Wang, & Espinoza, ) and in China (Liu, Bullock, & Coplan, ). Given the aforementioned positive value placed on academic achievement in China, we further speculated that academic difficulties might also be a precursor for peer victimization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation